1987
DOI: 10.1128/mcb.7.10.3663
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histone and beta A-globin gene expression during differentiation of chicken erythroid cells.

Abstract: The expression of the genes for several histones and pA-globin was examined in the chicken erythroid cell lineage. During the transition from CFU-(E) to the mature erythrocyte, histone H5 gradually increased fourfold in nuclei with little concomitant displacement of the Hi histones. This resulted in a 70% net increase in linker histone (Hi plus H5) content. The differential accumulation of H5 reflected (i) an increase in the transcriptional activity of the H5 gene occurring at the erythroblast stage, (ii) an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…The most dramatic effect of a H1 histone variant, histone H5, has been observed in chicken erythrocytes, where it is progressively deposited onto the chromatin as the erythrocyte matures (22,23). This process is marked by the concomitant loss of H1 histones already bound to the chromatin, condensation of the chromatin, and an increase in nucleosome spacing.…”
Section: Overexpression Of H1mentioning
confidence: 99%
“…The most dramatic effect of a H1 histone variant, histone H5, has been observed in chicken erythrocytes, where it is progressively deposited onto the chromatin as the erythrocyte matures (22,23). This process is marked by the concomitant loss of H1 histones already bound to the chromatin, condensation of the chromatin, and an increase in nucleosome spacing.…”
Section: Overexpression Of H1mentioning
confidence: 99%
“…Although the h5 gene is already set in an active chromatin conformation in early erythroid precursors (69), its transcription is not activated until the preerythroblast-to-erythroblast transition (2,72), coincident with the decline in the proliferation potential of the cells. The mechanisms that bring about transcriptional activation of the h5 gene are not fully elucidated but appear to reflect alterations in the balance between positive and negative effectors.…”
mentioning
confidence: 99%
“…Blots of total RNA from the same number of cells were hybridized with cDNA probes for H5, GATA-1, GATA-2, and GATA-3, labeled at comparable specific radioactivities. Figure 1OA (lane 1) shows that GATA-1 mRNA was, by and large, the most abundant mRNA in ND-HD3, followed by those of GATA-2 and GATA-3, the latter representing a relatively minor species. H5 mRNA, barely detectable in the autoradiography (lane 1), could be better seen when the blot was hybridized with the H5 probe alone.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to late erythroid markers, including the adult globin chains and cell surface proteins (2), H5 is already present in the early precursor CFU(E) (3,45), and its expression increases further with the onset of the expression of these late genes (1). Transcription run-on analysis of erythroid cells at different stages of maturation have also indicated that the activity of the H5 gene is lower in proliferating erythroid precursors than in more mature cells (1). Thus, H5 expression during maturation is predominantly regulated at the transcription level.…”
mentioning
confidence: 99%